Between Benefits and Legal Certainty: A Legal Analysis of the Raising of the One Piece Flag in Indonesia as a Form of Freedom of Expression - Ilyas Muttaqin; R. Adi Nurzaman (Manunggal Halim Jaya, 2026)
The raising of the Jolly Roger flag from the anime series One Piece in mid-2025 gave rise to significant normative tensions between the constitutional guarantee of freedom of expression and national security interests in Indonesia. This study examines the aspects of legal certainty and utility in this phenomenon using normative juridical methods with a conceptual and legislative approach. The analytical framework is based on Gustav Radbruch's theory of legal objectives and Lawrence Friedmann's theory of legal systems. The results of the study reveal a fundamental disparity in interpretation: the state applies a rigid security approach by qualifying the flag raising as an act of treason and provocation, while society interprets it as a legitimate symbolic social critique within the corridor of human rights. The criminalization of this expression is considered to have an inadequate legal basis, considering the absence of mens rea, the failure to fulfill the element of aanslag, and the inconsistency of the applied norms with the principle of lex certa. From a socio-legal perspective, law enforcement officers experience a cultural stuttering in distinguishing fictional symbols from real separatist threats. This study recommends a restorative justice approach as an alternative to criminalization, to prevent the chilling effect that undermines democratic space. The research's originality lies in its analysis of popular culture as a medium for social criticism within the Indonesian criminal law framework, an approach previously unexplored in domestic literature.